Transformasi Hukum Islam dalam Kerangka Pikir Ibnul Qayyim Al-Jauziyah - Rahman, Fathur (Tasamuh: Jurnal Studi Islam, 2019)
The dynamics of the transformation of Islamic law is a serious business in an effort to actualize syar'i prescriptions to be made operational guidance in the life of mankind, so that it appears clearly that Islamic law has really been set up practical life of mankind, not just talk at the level of ideal. It also can provide an understanding that religion has placed on its functional position, which certainly in a position like this would give more positive impact within the Muslim community. The possibilities of transformation within the Islamic law gives a strong indication that the teachings of Islam that was revealed to mankind is a religion that regulates all the joints of human life as well as to regulate the human within the scope of a different time and place. So that religious teachings should be applicated in any place and at any time.